Smart nanocarriers for drug delivery: controllable LSPR tuning - Lopatynskyi, A.M.; Lytvyn, V.K.; Mogylnyi, I.V.; Rachkov, O.E.; Soldatkin, O.P.; Chegel, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Gold nanostructures are considered as a potential platform for building smart nanocarriers that will form the basis of novel methods of targeted delivery and controlled release of drugs. However, to ensure maximum efficiency of gold nanoparticles upon the drug release via the plasmon-enhanced photothermal effect, it is necessary to optimize their spectral parameters for operation in the human body that requires both theoretical research and development of appropriate methods for nanostructures fabrication. In this work, mathematical modeling of light extinction spectral dependences for gold nanostructures of different morphology was performed to determine their geometric parameters that provide the occurrence of localized surface plasmon resonance (LSPR) in the red and near infrared regions of the spectrum, where the transparency window of biological tissues exists. Based on the results of previous studies and computer modeling, using hollow gold nanoshells to construct smart nanocarriers was found to be most reasonable. A protocol for production of these nanoparticles based on “silver-gold” galvanic replacement reaction, which is accompanied by a controlled shift of the LSPR wavelength position, was proposed and described in detail. It is shown that the loading of model biomolecules in hollow gold nanoshells significantly changes the output optical parameters of the system under investigation, which should be taken into account for matching with the laser excitation wavelength during the development of smart nanocarriers.